A GIS-Based Spatial Distribution Analysis of Road Traffic Accident Black Spots in Zaria, Kaduna State - Maliki, A. J.; Rifkatu, D.; Yunusa, A. (Journal of Spatial Information Sciences, 2025)
This study analyzed the spatial distribution of road traffic accident black spots in Zaria, Kaduna State, using data from the Federal Road Safety Commission (2006 – 2014) and field surveys. Accident locations were mapped using ArcGIS 10.1 with Kernel Density Estimation to identify high-risk zones. Results revealed black spots along Zaria-Kano Road (Yan Karfe, Dogarawa, Zabi, Anur Mosque) and Zaria-Sokoto Road (Polo Field, MTD, Palladan, Zango). The highest concentration of accidents occurred between 2012-2014, with 85% of fatalities along Zaria-Kano Road. Black spots were associated with poor road design and condition. The study recommends improved road infrastructure and emergency healthcare services at critical points.